Struktur dan Perkembangan Penelitian Dakwah Islam di Media Digital: Analisis Jaringan Literatur Sistematis Berdasarkan Scopus (2016–2026) (Jurnal Manajemen dan Pendidikan Agama Islam, 2026)
The development of digital media has transformed Islamic da’wah into a digitally mediated form of religious communication, reshaping structures of authority, engagement, and community formation. However, existing research remains fragmented and lacks a comprehensive structural map. This study conducted a Systematic Literature Network Analysis (SLNA) of Scopus-indexed publications on Islamic da’wah via digital platforms from 2016 to 2026. Using PRISMA-based screening techniques and bibliometric methods—including co-authorship, co-citation, and co-occurrence analyses with VOSviewer—the study analyzed 74 peer-reviewed journal articles. The results indicate a significant increase in the number of publications, particularly following the COVID-19 pandemic. The field is structured around four main themes: platform-based engagement strategies, youth identity formation, digital authority and ethics, and the adaptation of prophetic communication principles to the online context. Although Indonesia and Malaysia dominate the research output, the collaborative network remains relatively dispersed. New topics such as the influence of algorithms and AI-supported da‘wah suggest an expansion toward interdisciplinary directions. This study provides the first comprehensive map based on Scopus for research on Islamic digital da‘wah and offers a foundation for future theoretical and empirical development.